Sequential ultrastructural changes of the pancreas in zinc toxicosis in ducklings. - Kazacos, E. A. (1989)
The sequential ultrastructural alterations of the pancreas in zinc toxicosis were examined in ducklings fed 2500 ppm Zn (as ZnSO4) for 56 days. From days 3 to 17, acinar cells had cytoplasmic vacuoles that contained electron-dense, zymogen-like material and increased autophagocytosis. Other changes were swollen mitochondria and dilatation, vesiculation, degranulation and intracisternal sequestration of rough endoplasmic reticulum. Apoptosis was the predominant form of cell deletion. By day 10, acinar cellular atrophy and interstitial fibrosis were noted. Islets appeared normal. After day 19, the pancreas consisted of ductlike structures embedded in fibrous connective tissue with a minimal inflammatory cell response. These ductlike structures were lined by attenuated to cuboidal, atrophic acinar cells. Many cells contained granular, electron-dense cytoplasmic debris that served as a marker of previous cell damage. This ultrastructural study provides support for a previously proposed theory that ductlike structures (tubular complexes) arise by atrophy and dedifferentiation of acinar cells.